Current strategies for the targeted treatment of high-grade serous epithelial ovarian cancer and relevance of BRCA mutational status - Angiolo Gadducci; Valentina Guarneri; Fedro Alessandro Peccatori; Graziana Ronzino; Giuseppa Scandurra; Claudio Zamagni; Paolo Zola; Vanda Salutari (BMC, 2019)
Abstract Epithelial ovarian cancer is the most lethal gynecologic malignancy. In most women, it is diagnosed at an advanced stage, which largely explains the poor prognosis of this malignancy. Germline mutations of the genes BRCA1 and BRCA2, which encode proteins essential for the repair of double-strand DNA breaks through homologous recombination, lead to increased cancer predisposition. BRCA mutations are present in approximately 14% of epithelial ovarian cancers. Somatic BRCA mutations have also been described. Current first-line treatment of high-grade epithelial ovarian cancer includes debulking surgery followed by combination chemotherapy, usually carboplatin and paclitaxel. Ovarian cancer is highly sensitive to chemotherapy, in particular to platinum drugs. Most patient will achieve remission with initial chemotherapy, but most will eventually experience disease recurrence. Targeted therapies, including the anti-angiogenic agent bevacizumab and oral poly (ADP-ribose) polymerase (PARP) inhibitors, have been recently approved for the treatment of ovarian cancer, based on the results from randomized clinical trials showing significant benefits in terms of progression-free survival, with acceptable tolerability and no detrimental effects on quality of life. Olaparib, the first PARP inhibitor to be granted approval, is currently indicated as maintenance monotherapy in ovarian cancer patients with relapsed disease and mutated BRCA who have achieved a complete or partial response to platinum-based chemotherapy. The analysis of BRCA mutational status has, therefore, also become crucial for therapeutic decisions. Such advances are making personalized treatment of ovarian cancer feasible. Here we briefly review treatments for platinum-sensitive, high-grade serous epithelial ovarian cancer that are currently available in Italy, with a focus on targeted therapies and the relevance of BRCA mutational analysis. Based on the evidence and on current guidelines, we propose strategies for the tailored treatment of patients with relapsed ovarian cancer that take into account BRCA mutational status and the treatment received in the first-line setting.